2022
DOI: 10.1021/jacs.1c12596
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Metal–Organic Macrocycles: Synthesis, Characterization, and Electrical Conductivity

Abstract: The dimensional reduction of solids into smaller fragments provides a route to achieve new physical properties and gain deeper insight into the extended parent structures. Here, we report the synthesis of CuTOTP-OR (TOTP n− = 2,3,6,7tetraoxidotriphenylene), a family of copper-based macrocycles that resemble truncated fragments of the conductive twodimensional (2D) metal−organic framework Cu 3 (HHTP) 2 (HHTP = 2,3,6,7,10,. The planar metal−organic macrocycles self-assemble into ordered nanotubes with internal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 54 publications
5
68
0
Order By: Relevance
“…Besides, the strong characteristic peaks at about 1450 cm −1 in all cMOF samples correspond to a metal−semiquinone stretch, which is an intermediate state between the metal−quinone and catecholate complexes. 37 The intense band at ∼365 nm (intraligand π−π* transition) and the broader band at ∼640 nm (ligand-to-metal charge-transfer band) in the UV/vis spectra (Figure 1f) also correspond to a semiquinone assignment. 13,38,39 The ligand-to-metal charge-transfer tran-sition enables cMOFs to have the ability to conduct electricity at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Besides, the strong characteristic peaks at about 1450 cm −1 in all cMOF samples correspond to a metal−semiquinone stretch, which is an intermediate state between the metal−quinone and catecholate complexes. 37 The intense band at ∼365 nm (intraligand π−π* transition) and the broader band at ∼640 nm (ligand-to-metal charge-transfer band) in the UV/vis spectra (Figure 1f) also correspond to a semiquinone assignment. 13,38,39 The ligand-to-metal charge-transfer tran-sition enables cMOFs to have the ability to conduct electricity at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…The above-discussed spectroscopic characterizations, nonetheless, are unable to distinguish whether a Cu ion is Cu(I) or Cu(II) in the structures. In this case, GCPs 1 and 2 can be classified as Class III mixed-valence structures, [29][30] i.e., Creutz-Taube structures, according to the Robin-Day classification. 31 More importantly, we addressed a long-standing controversy about the oxidation states of metal ions in such 2D materials, and demonstrated that a periodic atomic structure could host a different number of electrons but remain charge-neutral.…”
Section: Resultsmentioning
confidence: 99%
“…4 In addition to higher mass transport rates, downsizing bulk MOFs to form colloidally stable nanocrystals may also provide important processability advantages. 5,6 This study focuses on controlling the morphology of Cu 3 (-HHTP) 2 (HHTP ¼ 2,3,6,7,10,11-hexahydroxytriphenylene), a prototypical 2D conductive metal-organic framework (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition to higher mass transport rates, downsizing bulk MOFs to form colloidally stable nanocrystals may also provide important processability advantages. 5,6…”
Section: Introductionmentioning
confidence: 99%